Bioinformatic Resources for Genomic Information Retrieval on Distributed Computing Approach - Arbex, Wagner; Costa, Leonardo Carvalho Nápolis; Fonseca, Leonardo Mariano Gravina; Silva, Camillo de Léllis Falcão da (Anais do Brazilian e-Science Workshop (BreSci), 2013)
The National Center for Biotechnology Information (NCBI) website provides computational resources from several web services, which can be reached with some programming languages and/or using specific modules of theses programming languages. Nevertheless, almost all services must be accessed from knowledge of metainformation about the data. Eventually, without knowing any information about what one wants to search, such as a single DNA sequence representing "string" by computational view, hindering access to NCBI's resources. This paper presents a bioinformatics resources to enable metainformation discovery of raw genomic data such as genetic sequences without any knowledge about them.